Tele-revista y la Transición : un programa de la televisión suiza para emigrantes españoles (1973-1989) - Calvo Salgado, Luis M. (Iberoamericana, 2015)
Tele-revista, a Swiss TV news program, was broadcasted in Spanish for Spanish emigrants living in Switzerland.